Dampak Penggunaan E Wallet terhadap Perilaku Belanja Mahasiswa dalam Perspektif Kemudahan dan Pengeluaran Impulsif - Fristia, Ananda; Dyah Ayu Megawaty (ARBITRASE: Journal of Economics and Accounting, 2025)
The rapid growth of digital financial technology in Indonesia, particularly digital wallet (e-wallet) services, has transformed the way people conduct transactions, especially among university students. Easy access, fast payment processes, and attractive promotional offers have made e-wallets a common payment method in daily activities. However, behind this convenience lies the potential for increased impulsive buying behavior, characterized by unplanned purchases. This study aims to analyze the effect of e-wallet usage on students’ impulsive buying behavior by examining perceived ease of use and impulsive spending as parallel mediating variables. A quantitative approach was employed involving 270 student respondents selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that e-wallet usage positively affects ease of use, impulsive spending, and impulsive buying behavior. Impulsive spending acts as a significant mediator, while ease of use does not serve as a mediating variable. These findings reinforce the Technology Acceptance Model (TAM) in the context of digital consumer behavior and highlight the importance of financial literacy and spending control features to help students use e-wallets more wisely and minimize excessive consumer behavior